2020
DOI: 10.1017/s1460396920000576
|View full text |Cite
|
Sign up to set email alerts
|

Using FFF beams to improve the therapeutic ratio of lung SBRT

Abstract: Aim: The aim of this study was to investigate the extent to which lung stereotactic body radiotherapy (SBRT) treatment plans can be improved by replacing conventional flattening filter (FF) beams with flattening filter-free (FFF) beams. Materials and methods: We selected 15 patients who had received SBRT with conventional 6-MV photon beams for early-stage lung cancer. We imported the patients’ treatment plans into the Eclipse 13·6 treatment planning system, in which we configured the AAA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…According to the RTOG 0813 recommendation ( 18 ), all of the SBRT plans had D 1500cc <12.5 Gy, D 1000cc <13.5 Gy and V 20 <10%. The use of FFF beams in lung SBRT treatment has been previously studied ( 6 , 15 , 30 ). Pokhrel et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the RTOG 0813 recommendation ( 18 ), all of the SBRT plans had D 1500cc <12.5 Gy, D 1000cc <13.5 Gy and V 20 <10%. The use of FFF beams in lung SBRT treatment has been previously studied ( 6 , 15 , 30 ). Pokhrel et al.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Vassiliev et al. ( 30 ) investigated dosimetric differences between FFF beams and FF beams, and reported that FFF beams achieved significantly better target coverage and OAR-sparing than FF beams. This dosimetric advantage of FFF beams was due to the lower out-of-field dose, more rapid dose fall-off, and softer energy spectrum removing the flattening filter compared to FF beams ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…The local control rate was 100% and none of the patients developed acute lung or rib toxicity. In a treatment planning study, Vassiliev et al 2 investigated lung SBRT treatments with 6-MV FF and 6-MV FFF beams for 15 patients. For the PTV, FFF plans improved several parameters: D 98 , D 95 , D 90 , the homogeneity index (HI), and uncomplicated tumour control probability (UTCP).…”
Section: Tps-based Studiesmentioning
confidence: 99%
“…A complete dosimetric analysis of the new FFF plans is given elsewhere. 2 The main finding was that by using FFF beams, doses to organs at risk could be lowered without compromising tumour coverage.…”
Section: Treatment Planningmentioning
confidence: 99%
See 1 more Smart Citation